Overweight, Alcohol, and Tobacco Consumption Are Associated with Hypertension among Police and Military Personnel: A Meta-Analysis - Firman Pardosi; Setyo Sri Rahardjo; Yulia Lanti Retno Dewi (Journal of Epidemiology and Public Health, 2020)
Background: Increased blood pressure for a long time can increase the risk of kidney failure, coronary heart disease, brain damage, and other diseases. In 2019, it is estimated that hypertension is experienced by 1.13 billion people in the world with most (two thirds) living in low and middle income countries. Other study also shows that the police and military are at risk of developing hypertension due to a number of factors such as low know-ledge about healthy and nutritious food, co-workers who are smokers, and consuming alcohol. This study aimed to analyze the risk factors for hypertension in the police and military in the world using meta analysis.Subjects and Method: This was a meta-analysis and systematic review. The articles used were obtained from Google Scholar, Springer Link, ProQuest, and Science Direct databases. Selected articles published from 2000 to 2020. Keywords to search for articles are as follows: hypertension police personnel and military, or hypertension police personnel and military. The articles studied are 3 full text articles with cross sectional study designs and 1 full text articles with case control study design. Articles are collected using PRISMA diagrams, and analyzed using the Review Manager application 5.3.Results: Overweight (aOR= 1.42; 95% CI = 1.01 to 2.00; p= 0.04), alcohol consumption (aOR= 1.55; 95% CI= 1.12 to 2.12; p= 0.007), cigarette consumption (aOR= 1.45 ; 95% CI= 1.06 to 1.97; p= 0.020) is a risk factor for hypertension in the police and military.Conclusion: Overweight, alcohol consumption, and cigarette consumption, are risk factors for hypertension in police and military personnel.Keywords: overweight, alcohol, smoking, hypertension, meta analysisCorrespondence: Firman Pardosi. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: pardosi.fp@gmail.com.Mobile: +6285261423865.Journal of Epidemiology and Public Health (2020), 05(01): 88-96https://doi.org/10.26911/jepublichealth.2020.05.01.09.